How do teachers exercise relational agency for supporting migrant students within social networks in schools from Scotland, Finland, and Sweden? - Pantić, Nataša (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study examines how teachers exercise relational agency - working flexibly with other actors in their social networks to support migrant students. Teachers and other staff members from 7 schools in Scotland, Finland and Sweden participated in social network surveys (n = 1116), online logs (n = 275) and interviews (n = 82). A mixed-method social network analysis shows how networks facilitate relational agency as teachers reach out to others to mobilise resources and tacit knowledge within their school communities. The findings point to the critical role of professional collaboration and suggest that social networks shape how teachers work with specialists to support migrant students.